Effects of Rapamycin Combined with Cisplatin on Tumor Necrosis Factor TNF-α in MG-63 Cells. (16th July 2020) - Han, Tian-Yu; Ma, Bin; Hu, Bing; Xiang, Liang-Bi; Liu, Xin-Wei
Rapamycin (RAPA) and cisplatin (CDDP) are used as clinical drugs in the treatment of various tumors, but there are few studies on the combination of RAPA and CDDP. Tumor necrosis factor α (TNF-α) plays an important role in tumorigenesis and development. This study is to explore the effects of RAPA combined with CDDP on the expression of TNF-α in osteosarcoma MG-63 cells. MG-63 cells were routinely cultured and divided into a control group, a RAPA group (20 μM), a CDDP group (20 μM), and a RAPA + CDDP group (20 μM + 20 μM). The four groups were treated with drugs for 24 and 48 h, respectively. Real-time polymerase chain reaction (PCR), Western blot (WB), and immunocytochemistry (ICC) were adopted to detect the expression of TNF-α gene and protein. The results of PCR showed that both the separate drug use and drug combination could significantly lower the relative expression quantity of TNF-α gene (* P < 0.5), but the combination was more effective (* P < 0.5); the expression quantity of TNF-α gene in the RAPA + CDDP group at 48 h was much lower than that at 24 h (*** P < 0.001). The results of WB showed that both the separate drug use and drug combination could significantly lower the relative expression quantity of TNF-α protein, and the combination was more effective than separate drug use (* P < 0.05) and more effective at 48 h (*** P < 0.001); the expression quantity of TNF-α protein in the same group at 48 h was much lower than that at 24 h (* P < 0.05). The results of ICC showed that both the separate drug use and drug combination could significantly lower the relative expression quantity of TNF-α protein, and the combination was more effective than separate drug use (** P < 0.01) and more effective at 48 h (*** P < 0.001); the expression quantity of TNF-α protein in the same group at 48 h was much lower than that at 24 h (** P < 0.01). RAPA combined with CDDP can significantly reduce the expression of TNF-α in MG-63 cells, which is time dependent.